The Influence of Motivational Interviewing with Spiritual Approach to the Hopelessness and Motivation of A Patient ESRD which Helpes Regular Hemodialisis - Kusumawardani, Diny; Muhsinin, Siti Zuraida; Pujiningsih, Erniawati (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Various problems arising from the failure of the kidney on the client premises terminal renal failure above can lead to the emergence of despair and decreased motivation to recover. One way to overcome the problem is with motivational interviewing interventions with spiritual approach (thanksgiving, patient and sincere). The purpose of this study is to determine the effect of motivational interviewing on despair and motivation to recover ESRD patients undergoing regular hemodialysis. This research uses quasy experiment with pre-post test design and posttest only with control group design. The random sampling technique is simple. The sample was 32 respondents based on the inclusion criteria. Intervention is done for 4 weeks with 2 meetings / week. Independent variable of this research is motivational interviewing with spiritual approach. Dependent variable is hopelessness and motivation to recover. This study uses questionnaire instruments to measure despair and motivation to recover, which had previously been tested for validity and reliability. Statistical test using paired t test, independent t test, mann whitney and wilcoxon signed rank test. The result of statistical test showed that MI with spiritual approach had an effect on decrease of hopelessness (p = 0,001) and increase of motivation to recover (p = 0,001). The MI intervention helps the patient in identifying, evaluating and responding to deformities of his mind and beliefs. Helping the patient develop a rational mindset, engaging in reality tests, and reshaping behavior by altering internal messages. MI interventions with a spiritual approach affect the decrease of hopelessness and increased motivation to recover in ESRD patients with regular HD.